Waiting to Vote in the 2016 Presidential Election: Evidence from a Multi-county Study. (June 2020) - Stein, Robert M.; Mann, Christopher; Stewart, Charles; Birenbaum, Zachary; Fung, Anson; Greenberg, Jed; Kawsar, Farhan; Alberda, Gayle; Alvarez, R. Michael; Atkeson, Lonna; Beaulieu, Emily; Birkhead, Nathaniel A.; et al.
This paper is the result of a nationwide study of polling place dynamics in the 2016 presidential election. Research teams, recruited from local colleges and universities and located in twenty-eight election jurisdictions across the United States, observed and timed voters as they entered the queue at their respective polling places and then voted. We report results about four specific polling place operations and practices: the length of the check-in line, the number of voters leaving the check-in line once they have joined it, the time for a voter to check in to vote (i.e., verify voter's identification and obtain a ballot), and the time to complete a ballot. Long lines, waiting times, and times to vote are closely related to time of day (mornings are busiest for polling places). We found the recent adoption of photographic voter identification (ID) requirements to have a disparate effect on the time to check in among white and nonwhite polling places. In majority-white polling places, scanning a voter's driver's license speeds up the check-in process. In majority nonwhite polling locations, the effect of strict voter ID requirements increases time to check in, albeit modestly.